Weight concerns scale applied to college students: comparison between pencil-and-paper and online formats - Dias, Juliana Chioda Ribeiro [UNESP]; Maroco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (SAGE Publications, 2015)
Online data collection is becoming increasingly common and has some advantages compared to traditional paper-and-pencil formats, such as reducing loss of data, increasing participants' privacy, and decreasing the effect of social desirability. However, the validity and reliability of this administration format must be established before results can be considered acceptable. The aim of this study was to evaluate the validity, reliability, and equivalence of paper-and-pencil and online versions of the Weight Concerns Scale (WCS) when applied to Brazilian university students. A crossover design was used, and the Portuguese version of the WCS (in both paper-and-pencil and online formats) was completed by 100 college students. The results indicated adequate fit in both formats. The simultaneous fit of data for both groups was excellent, with strong invariance between models. Adequate convergent validity, internal consistency, and mean score equivalence of the WCS in both formats were observed. Thus, the WCS presented adequate reliability and validity in both administration formats, with equivalence/stability between answers.